2005
DOI: 10.1159/000089658
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Injure Themselves?

Abstract: The aim of this study was to evaluate a questionnaire for the assessment of immediate functions of self-injurious behavior (SIB). SIB is defined as deliberate injuries of the skin such as burning, cutting or beating. Suicidal attempts as well as self-injuries for aesthetic reasons were excluded. Immediate functions were collected from the literature as well as from statements of SIB sufferers. Finally, 154 questions with the response options ‘right’, ‘wrong’ and ‘unknown’ – for phenomena people did not know – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
(17 reference statements)
3
5
0
Order By: Relevance
“…It would suggest that Millon's instruments are useful for detection of adolescents with high DSH risk [25] . In this sense, we have found that inhibited-affected inmates presented a greater tendency towards psychopathology, DSH and avoidance coping, data that were in accordance with those of other studies that indicated the connection between psychopathology, passive and avoidance coping strategies, and also with DSH in the hospital and prison populations [26][27][28] .…”
Section: Discussionsupporting
confidence: 91%
“…It would suggest that Millon's instruments are useful for detection of adolescents with high DSH risk [25] . In this sense, we have found that inhibited-affected inmates presented a greater tendency towards psychopathology, DSH and avoidance coping, data that were in accordance with those of other studies that indicated the connection between psychopathology, passive and avoidance coping strategies, and also with DSH in the hospital and prison populations [26][27][28] .…”
Section: Discussionsupporting
confidence: 91%
“…The marked variation between individuals in their motives for and effects gained from DSH replicates similar reports in the literature (Haas & Popp, 2006;McAllister, 2003). These different motives appeared to map onto the subjective experience of using self-administered acupuncture and have important implications for other studies of interventions for DSH.…”
Section: Discussionsupporting
confidence: 76%
“…Klonsky and Glenn (2009) classified the functions of NSSI as intrapsychic and interpersonal. Many researchers (Haas & Popp 2006, Klonsky 2009, Nock 2009, Polk & Liss 2007, Scoliers et al 2009 demonstrated that the most frequently favored intrapsychic function of NSSI is affect regulation. This function refers to coping with negative thoughts and emotions; reducing or evading them.…”
Section: Discussionmentioning
confidence: 99%